Stroke as Presenting Feature of COVID-19 in a Pediatric Patient - Swartwood, Shanna; Nelson, Gary R.; Espinoza, Audie C. (Journal of Pediatric Neurology, 2021)
Neurologic manifestations of severe acute respiratory syndrome coronavirus 2, the virus responsible for novel coronavirus 2019 (COVID-19) infection, have been frequently reported in the adult population but remain relatively rare in pediatric patients, specifically in regard to cerebrovascular accidents (CVAs). We present the case of a previously healthy 16-year-old adolescent boy with no preceding infectious symptoms who developed acute onset of left-sided weakness and slurred speech subsequently diagnosed with acute ischemic stroke (AIS). After performing a thorough diagnostic work-up, no clear etiology for AIS was identified. He was found to be COVID-19 positive by reverse transcription polymerase chain reaction upon admission. Accumulating evidence supports a link between COVID-19 and a systemic prothrombotic state suggesting pediatric patients who present with AIS and no other risk factors should be screened for this novel virus and potentially for extracranial sources of thrombi. As the rates of positive COVID-19 infection increase in the pediatric population, pediatricians and other pediatric subspecialists should be aware of the potential neurological and cerebrovascular complications of this novel virus to avoid delays in evaluation and intervention.
Keywords: pediatric; stroke; COVID-19